Preventing and reducing patient harm using two safety frameworks. - Oyebode Dosunmu (Christian Journal for Global Health)
A patient safety field has emerged due to observed increased patient harm in healthcare institutions. Such preventable harms are becoming a danger to patient care. They have resulted in the death of patients on many occasions. Therefore, there is a need to intensify efforts to reduce preventable harm in healthcare institutions.This is a case report of a typical, preventable harm from non-steroidal anti-inflammatory drug (NSAID) misuse that occurred in a healthcare institution. It analyzes the case for future prevention. The events leading to the harm are explained, and interrelated factors causing the harm are detailed.The System Engineering Initiative for Patient Safety (SEIPS) and Measurement and Monitoring of Safety Framework (MMSF) were used to analyze the case and provide recommendations for preventing and reducing such preventable harms and other related harms in the future.More efforts should be targeted towards preventing and reducing cases of patient harm. Institutionalizing the field of patient safety and patient safety officers’ role in healthcare institutions, especially in developing countries, is recommended.